Cystic fibrosis newborn screening: outcome of infants with normal sweat tests. Issue 8 (7th November 2017) - Edmondson, Claire; Grime, Christopher; Prasad, Ammani; Cowlard, Jacqui; Nwokoro, Chinedu E C; Ruiz, Gary; Wallis, Colin; Balfour-Lynn, Ian M
Abstract : Newborn babies positively screened for cystic fibrosis (CF) (high serum immunoreactive trypsin (IRT) with DNA analysis) are referred for a diagnostic sweat test, which may be normal (sweat chloride <30 mmol/L). Unless two gene mutations are identified during Newborn screening (NBS), the babies are discharged from follow-up. We wished to check that none had subsequently developed symptoms suggestive of CF. We retrospectively reviewed patient notes and contacted general practitioners of all babies with a negative sweat test, conducted in one of the four paediatric specialist CF centres in London, over the first 6 years of screening in South East England. Of 511 babies referred, 95 (19%) had a normal sweat test. Five (5%) had CF diagnosed genetically, two of them on extended genome sequencing after clinical suspicion. Eleven (12%) were designated as CF screen positive inconclusive diagnosis (CFSPID); one of the five CF children was originally designated as CFSPID. Seventy-nine (83%) were assumed to be false-positive cases and discharged; follow-up data were available for 51/79 (65%); 32/51 (63%) had no health issues, 19/51 (37%) had other significant non-CF pathology. These results are reassuring in that within the limitations of those lost to follow-up, CF symptoms have not emerged in the discharged children. The high non-CF morbidity in these children may relate to known causes of high IRT at birth. Clinicians need to be aware that a child can have CF despite a normal sweat test following NBS, and if symptoms suggest the diagnosis, further testing, including extended genome sequencing, is required.